2016
DOI: 10.1002/eco.1799
|View full text |Cite
|
Sign up to set email alerts
|

From facilitative to competitive interactions between woody plants and plants with crassulacean acid metabolism (CAM): The role of hydraulic descent

Abstract: Woody plants may facilitate the establishment of seedlings with crassulacean acid metabolism (CAM) by ameliorating the abiotic environment through an increase in soil water availability. Because of the low transpiration rate in shallow‐rooted CAM plants and the consequently high soil water contents in the shallow soil, deep‐rooted trees in tree–CAM associations could perform hydraulic descent transporting water from wetter shallow soil to drier deep soil in arid environments. It remains unclear, however, wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
(197 reference statements)
0
5
0
Order By: Relevance
“…Typically, HR occurs during the night, when transpiration has ceased [3][4][5]. Water can be redistributed in the upward (i.e., hydraulic lift [2,6,7]), downward (i.e., hydraulic descent [8][9][10][11]), and lateral directions [12][13][14][15]. Field observations showed that HR plays an important role in terrestrial ecohydrological cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, HR occurs during the night, when transpiration has ceased [3][4][5]. Water can be redistributed in the upward (i.e., hydraulic lift [2,6,7]), downward (i.e., hydraulic descent [8][9][10][11]), and lateral directions [12][13][14][15]. Field observations showed that HR plays an important role in terrestrial ecohydrological cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the interest that facilitation exhibits from the perspective of basic biological knowledge, it has serious implications for soil surface water, degraded land restoration (Antonio et al, 2018;Víctor et al, 2017), as well as for agriculture and food security (Li et al, 2014;Moschitz et al, 2015). To that end, understanding the interplay between trees and the way they ameliorate their biotic and physical environment (Yu and D'Odorico, 2017) as well as climate and soil, is critical for ecosystem management, agricultural planning, and water management (Davis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such hydraulic redistribution (HR) of soil water via plant roots can be upward (hydraulic lift), downward (hydraulic descent), or lateral (Horton & Hart, 1998;Neumann & Cardon, 2012;Prieto et al, 2012;Sardans & Peñuelas, 2014;Yu & D'Odorico, 2017). Such hydraulic redistribution (HR) of soil water via plant roots can be upward (hydraulic lift), downward (hydraulic descent), or lateral (Horton & Hart, 1998;Neumann & Cardon, 2012;Prieto et al, 2012;Sardans & Peñuelas, 2014;Yu & D'Odorico, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In seasonally dry ecosystems, plant roots transfer water from moist soil layers to dry soil layers along the soil water potential gradient. Such hydraulic redistribution (HR) of soil water via plant roots can be upward (hydraulic lift), downward (hydraulic descent), or lateral (Horton & Hart, 1998;Neumann & Cardon, 2012;Prieto et al, 2012;Sardans & Peñuelas, 2014;Yu & D'Odorico, 2017). The effects of HR on the hydrological, carbon, and nitrogen cycles have been demonstrated in numerous field studies (e.g., Cardon et al, 2013;Ryel et al, 2002;Scott et al, 2008).…”
Section: Introductionmentioning
confidence: 99%